2009
DOI: 10.1252/jcej.08we184
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Gas Holdup and Oxygen Transfer in Three-Phase Circulating Fluidized-Bed Bioreactors with Swirling Flow

Abstract: Enhancement of gas holdup and oxygen transfer was investigated in the riser of a three-phase circulating fluidized bed, with a diameter of 0.102 m (ID) and a height of 3.5 m, by means of liquid swirling flow. Effects of gas (0.01-0.07 m/s) and liquid (0.17-0.44 m/s) velocities, fluidized solid particle size (1.0, 1.7, 2.1, 3.0 mm), solid circulation rate (2-8 kg/(m 2 s)) and swirling liquid ratio (0-0.5) on the gas holdup and volumetric oxygen transfer coefficient in the riser were examined. The gas holdup and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…However, the increase in the liquid velocity results in the increase in the liquid holdup, which causes to the decrease in the gas holdup in the column. Those trends agree well with the results of other investigations [8,9,18]. The complicated flow behavior of bubbles in the bubble column can be described by means of the drift flux model which was suggested by Zuber and Findley [19].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, the increase in the liquid velocity results in the increase in the liquid holdup, which causes to the decrease in the gas holdup in the column. Those trends agree well with the results of other investigations [8,9,18]. The complicated flow behavior of bubbles in the bubble column can be described by means of the drift flux model which was suggested by Zuber and Findley [19].…”
Section: Resultssupporting
confidence: 91%
“…In addition, the liquid side true mass transfer coefficient should be verified, since the resistance in the gas phase for the mass transfer has been understood to be negligible [1][2][3][4]. However, various kinds of investigations have focused on the overall volumetric mass transfer coefficients, and the values of interfacial area between the contacting two phases have been estimated from a knowledge of the bubble size and its holdup indirectly [5][6][7][8][9]. In the present study, the interfacial area and liquid side true mass transfer coefficient in addition to the overall volumetric mass transfer coefficient were determined directly by resorting to the simultaneous physical desorption of O 2 and chemical absorption of CO 2 [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The solid circulation rate (G S ), which was measured at least three times, was determined by measuring the amounts of particles piled up above the butterfly valve in the solid recycle device [10][11][12][13][14][15] in a given steady state condition. The measured values of G S agreed well with each other within 3~4% deviations.…”
Section: Methodsmentioning
confidence: 99%
“…(Cho et al, 2001a;Wang et al, 2001a); however, the local ε G showed a local maximum sometimes with increasing U L (Cao et al, 2009). The averaged value of ε G was found to increase with increasing U G (Wang et al, 2001a;Liu et al, 2003;Son et al, 2007aSon et al, , 2007bSon et al, , 2009 or d P (Son et al, 2009) but decrease with increasing μ L ; however, it decreases or does not change considerably with increasing U L or G S (Wang et al, 2001a;Liu et al, 2003;Son et al, 2007aSon et al, , 2007bSon et al, , 2009, as shown in Figure 5. Son et al (2009) tried to enhance the ε G in the riser by injecting the auxiliary liquid by means of swirling flow.…”
Section: Three-phase Circulating Uidized Beds (Tpcfbs)mentioning
confidence: 79%
“…The complicated flow behaviors were analyzed with adopting the stochastic methods, by choosing the pressure as an independent variable. The pressure fluctuations were analyzed by means of phase space portraits and Kolmogorov entropy (Cho et al, 2001a;Son et al, 2007b) to predict the overall and resultant flow behaviors in the riser. The phase space portraits of pressure fluctuation time series could visualize the complex flow behaviors of multiphase in the riser.…”
Section: Three-phase Circulating Uidized Beds (Tpcfbs)mentioning
confidence: 99%